SEARCH FOR GENETIC PREDICTORS OF PREECLAMPSIA: MODERN APPROACHES TO EARLY DETECTION AND PREVENTION - Shamsiyeva Z. I. (Journal Park Publishing, 2025)
Preeclampsia is a severe complication of pregnancy characterized by hypertension and multiple organ disorders, which remains one of the leading causes of maternal and perinatal morbidity. The pathogenesis of the disease is caused by a complex interaction of factors, among which vascular tone disorders, endothelial dysfunction and disorders of the blood coagulation system are of particular importance. In recent years, special attention has been paid to genetic factors that can serve as predictors of the risk of developing preeclampsia, which makes it possible to increase the effectiveness of its prevention and timely take therapeutic measures.
Keywords: Preeclampsia, endothelial dysfunction, hemostasis system, genetic markers.